Recurrent Malignant Fibrous Histiocytoma in the Left Parietal Region of Cranium: A Case Report - Rahman, ML; Ali, ASM Shawkat (TAJ: Journal of Teachers Association, 2009)
A male of 20 years of age presented with features of intracranial space occupying lesion of cranium involving the brain. He came with the history of previous surgery in the head one-year back. On operation, an osteolytic growth from the skull bone invading the meninges and brain parenchyma. Who found Histopathological report revealed malignant fibrous histiocytoma. doi: 10.3329/taj.v17i1.3492 TAJ 2004; 17(1) : 55-56